2014
DOI: 10.4274/turkderm.46338
|View full text |Cite
|
Sign up to set email alerts
|

Is the HLA B27 genotype a risc faktor for psoriatic arthritis and psoriasis vulgaris?

Abstract: Backround and Design:Psoriasis is a common inflammatory dermatological disease which may be complicated with joint involvement. It has been suggested that there is an association between HLA-B27 positivity and early onset psoriasis. The purpose of the current study was to investigate the incidence of HLA-B27 positivity in psoriasis patients with arthritis. Materials and Methods: In a total of 96 patients with psoriasis, age of onset, family history, and Psoriasis Area and Severity Index (PASI) values were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In Turkish population, we have found that HLA-B27 positivity increased the risk of psoriasis and psoriatic arthritis 5 to 10 times more, respectively [97]. There are various molecular-based hypotheses such as molecular mimicry, defective immunity, heavy chain folding incorrectly, and deterioration of HLA-B27 allele for relationship between HLA-B27 and psoriatic arthritis (PsA) [97].…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…In Turkish population, we have found that HLA-B27 positivity increased the risk of psoriasis and psoriatic arthritis 5 to 10 times more, respectively [97]. There are various molecular-based hypotheses such as molecular mimicry, defective immunity, heavy chain folding incorrectly, and deterioration of HLA-B27 allele for relationship between HLA-B27 and psoriatic arthritis (PsA) [97].…”
Section: Psoriatic Arthritismentioning
confidence: 99%